Project citizen digital: A learning model of civic education in digital age - Dahliyana, Asep; Cahyati, Sri; Warlim, Warlim; Rahmasari, Nandha; Dianti, Nenden Hilpa (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
Civic education plays a crucial role in fostering responsible citizenship and developing comprehensive civic competencies. In Indonesia, it holds a strategic position as a compulsory subject mandated by the government and implemented across all universities. This study aims to investigate the impact of Project Citizen Digital on students’ civic competency in higher education. Employing a quantitative approach, the research focuses on the implementation and evaluation stages of the ADDIE model following the development of the Project Citizen Digital application. A one-group pretest–posttest design was used to assess changes in students’ civic competency before and after the intervention. The study involved 480 undergraduate students from Universitas Pendidikan Indonesia, consisting of 400 students in the first cohort and 80 students in the second. Data were analyzed using paired-sample statistical tests through SPSS. The findings indicate a statistically significant improvement in students’ civic competency after engaging in Project Citizen Digital-based learning. This is evidenced by a Sig. (2-tailed) value of 0.000, which is lower than 0.025, leading to the rejection of the null hypothesis. The results confirm that the intervention produced a meaningful difference between pretest and posttest scores. Therefore, Project Citizen Digital demonstrates strong potential as an innovative and effective model for integrating digital technology with participatory civic learning in higher education.